2017
DOI: 10.1186/s13098-017-0226-0
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase-4 levels are increased and partially related to body fat distribution in patients with familial partial lipodystrophy type 2

Abstract: BackgroundDipeptidyl peptidase-4 (DDP4) is an enzyme responsible for glucagon-like peptide-1 inactivation and plays an important role in glucose metabolism.ObjectiveThe aim of this study was to evaluate DPP4 levels in patients with familial partial lipodystrophy type 2 (FPLD2) and correlate it with body fat distribution.MethodsFourteen patients with FPLD2 were selected to participate in this study and matched to a healthy control group (n = 8). All participants had anthropometrical data registered. Body adipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
(23 reference statements)
3
10
0
Order By: Relevance
“…In addition to the expected insulin resistance, we identified a defect of first-phase insulin secretion in the woman, which may explain the efficacy of the GLP-1 receptor agonist; however, this has not been directly confirmed. Our findings may be related to the increased levels of dipeptidyl peptidase-4 found in familial partial lipodystrophy type 2, as recently reported [6]. The effectiveness of liraglutide has also been demonstrated in a retrospective case-control study of patients with HIV-associated lipodystrophy; however, in that case, the effects on glycaemia were small and probably secondary to weight loss, which was different from our case [7].…”
Section: What's New?supporting
confidence: 59%
See 1 more Smart Citation
“…In addition to the expected insulin resistance, we identified a defect of first-phase insulin secretion in the woman, which may explain the efficacy of the GLP-1 receptor agonist; however, this has not been directly confirmed. Our findings may be related to the increased levels of dipeptidyl peptidase-4 found in familial partial lipodystrophy type 2, as recently reported [6]. The effectiveness of liraglutide has also been demonstrated in a retrospective case-control study of patients with HIV-associated lipodystrophy; however, in that case, the effects on glycaemia were small and probably secondary to weight loss, which was different from our case [7].…”
Section: What's New?supporting
confidence: 59%
“…Our findings may be related to the increased levels of dipeptidyl peptidase-4 found in familial partial lipodystrophy type 2, as recently reported [6]. In addition to the expected insulin resistance, we identified a defect of first-phase insulin secretion in the woman, which may explain the efficacy of the GLP-1 receptor agonist; however, this has not been directly confirmed.…”
Section: Discussionsupporting
confidence: 42%
“…These findings are in consistence with previous studies [42,43]. Regarding the central obesity, Valerio et al demonstrated a positive correlation between DPP-4 enzyme levels and central fat distribution in patients with familial partial lipodystrophy type 2 [44]. Thus, inhibition of DPP-4 enzyme may be associated with central fat redistribution and waist circumference reduction.…”
Section: Discussionsupporting
confidence: 90%
“…A link between obesity or underlying diseases like diabetes mellitus, which both can affect DPP4 expression levels [48], and the risk of fatal outcome of MERS-CoV infection has been made [49]. Moreover, alanine scanning mutagenesis identified DPP4 residues critical for MERS-CoV entry, including K267, L294, I295, R317 and R336 [50,51]. However, the impact of natural-occurring variations on host cell entry of MERS-CoV has not been addressed so far.…”
Section: Discussionmentioning
confidence: 99%